Filsafat Pendidikan dalam Perspektif Islam dan Relevansinya dengan Pendidikan Pesantren di Indonesia - Endah Permanasari; Ayu Setiawati; Dena Rizka Fitria; Siti Roudhotul Jannah (KURAS Institute, 2023)
The purpose of this study is to explain the concepts related to the philosophy of education from an Islamic perspective. Additionally, this article connects these philosophical concepts to the general phenomenon of Islamic boarding school education in Indonesia. To achieve its objectives, the study employs a literature review method, which includes activities such as collecting data from libraries, reading, evaluating, and organizing information gathered from various literature sources.The ideology of Islamic education is explained using a qualitative descriptive approach, with published academic texts serving as the primary references. Based on the analysis, it is concluded that ontologically, Islamic educational philosophy views humans as creations of Allah who possess the inherent potential for development. Epistemologically, the sources of knowledge in Islam extend beyond reason and experience, encompassing revelation through the Qur'an and Sunnah. From an axiological perspective, Islamic education aims to instill ethical and moral values that underpin all human activities. Furthermore, the Islamic boarding school education system exemplifies these principles within the context of Indonesia. The relevance of Islamic boarding schools in addressing the challenges of modern education is significant, particularly in nurturing a generation that is not only academically intelligent but also morally upright.